Uso do álccol e outras drogas entre homens que fazem sexo com homens em três centros urbanos do estado do Ceará - Silva, João Marcos de Meneses e (2005)
Background: Binge drinking has been associated with risk behavior in the population of men who have sex with men (MSM). No previous studies have been conducted in Brazil in this population. Methods: This is a cross-sectional study where men reporting oral or anal sex with other men in the past six months were interviewed. The subjects were from Fortaleza (400), Sobral (100) and from the Cariri area – Juazeiro to Norte, Barbalha or Crato (100). Univariate and multivariate analyses have been carried out to evaluate risk factors associated with binge drinking. Results: 63% of the MSM participants were classified as binge drinkers, a percentage much higher than the one observed in American studies. It has been shown that the increasing consumption of alcohol leads to an increase in the simultaneous use of other licit or illicit drugs. The predictors connected with binge drinking are: age, 21-30 vs. <21 years old (OR: 1,5; 95%CI: 1,1-2,9); >30 vs.<21 years old (OR: 1.6; 95%CI: 1.2 – 2.3); civil status, being single/separated/divorced vs. being married/together (OR: 3.0; 95%CI: 1.7-5.3); race, being black vs. white (OR: 5.9; 95%CI: 1.7-20.1); being mixed vs. white (OR: 1.8; 95% CI: 1.3-2.6); getting paid for sex (OR: 2.0; 95%CI: 1.4-3.0); having had an HIV test (OR: 1.7; 95% CI: 1.3-2.2); family disapproval of MSM (OR: 1.4; 95%CI: 1.1-1.9); using vs. not using any drug (OR: 2.3; 95%CI: 1.8-29). The findings of this study show the importance of alcohol abuse as a public health problem in this specific population and the need for prevention measures. The relationship between reported binge drinking and risky sex is anomalous and requires further exploration.